Tracing the Roots of Ascribed Tharu Identity in the Context of Nepal - Chaudhary , Nathu Ram (BMC Research Journal, 2026)
Tharus, an indigenous people of Nepal, spread throughout Tarai and inner Tarai of Nepal. There is the controversial understanding on origin of the Tharus of Nepal. This paper aims to review the various anthropological and other literatures regarding the origin of Tharus of Nepal, one of the oldest ethnic people of Nepal.This article employs a tripartite sociological framework—Prescribed, Ascribed, and Described identity—to analyze how Tharus in 22 districts navigate their status in a federalizing Nepal. Throughout the course of the past century, numerous academic articles have been dedicated to exploring the intricacies of the Tharu ethnic group. These publications have delved into various aspects of their society, including social structure, economy, women's roles, religious practices and customs, folklore, homes, and demographics. However, a significant gap remains in our understanding of the Tharu language, its dialects, and the sociolinguistic factors that shape it. The history of the Tharu origin tells that there are prescribed, described and ascribed identities. Because of these differences, Tharu students face an identity crisis. So, I have critically analyzed the history from various lenses to challenge the prescribed and described Tharu identities by the ascribed identity in the curriculum. Thematically, I argue the origin of the Tharus connection with the vedic era. This study will helpful for opening the way of studying the various aspect of Tharus in Nepal.